Linguistic Validation of the Irritable Bowel Syndrome-Quality of Life Questionnaire for Iranian Patients - Ali Gholamrezaei; Behzad Zolfaghari; Ziba Farajzadegan; Kianoosh Nemati; Hamed Daghaghzadeh; Hamid Tavakkoli; Mohammad Hassan Emami (Acta Medica Iranica, 2011)
There is a growing interest of clinical and epidemiological researches in the field of functional gastrointestinal disorders in our society. Accordingly, validated and culturally adapted instruments are required for appropriate measurement of variables specially the quality of life. The aim of our study was the linguistic validation of the Irritable Bowel Syndrome-Quality of Life questionnaire (IBS-QOL) for Iranian IBS patients with Persian language. Following the standard forward-backward translation method, the IBS-QOL was translated into the Persian language and completed by 141 IBS patients. Patients also completed the IBS Symptom Severity Scale (IBS-SSS) and Hospital Anxiety and Depression Scale (HADS). One-week retest was performed on 30 randomly selected patients. Internal consistency and test-retest reliability were assessed using Cronbach's alpha and intraclass correlation coefficient (ICC), respectively. To analyze the discriminant validity, the IBS-QOL scores was correlated to the IBS-SSS and HADS scores. According to the results, reliability analyses were acceptable for all of the IBS-QOL domains (Cronbach's alpha=0.68 to 0.90 and ICCs=0.77 to 0.91). Discriminant validity was supported by the presence of correlations of the IBS-QOL scores with disease severity (r = -0.628), depression (r = -0.692), and anxiety (r = -0.711) scores; P < 0.001. These results indicate that the Persian version of the IBS-QOL is a reliable instrument with sufficient psychometric requirements to assess quality of life in Iranian IBS patients with Persian language.